Β-Tricalcium phosphate/ԑ-polycaprolactone composite scaffolds with a controllable gradient: Fabrication and characterization. Issue 13 (September 2019) - Wu, Yanlong; Chen, Xu; Zhao, Guangbin; Chen, Ruomeng; Liu, Yongcai; Ren, Hui; Qu, Xiaoli; Liu, Yaxiong
Abstract: β-tricalcium phosphate (β-TCP)/ԑ-polycaprolactone (PCL) composite scaffolds with a controllable gradient were developed with a two-step process: fabrication of the β-TCP scaffolds using digital light processing (DLP) 3D printing and then immersion of the β-TCP scaffolds into a PCL melt for different times. The gradient structure was controlled by the immersion time of the β-TCP scaffolds in the molten PCL. The composite scaffolds with a gradient exhibited a substantially higher compressive strength and toughness than the bare β-TCP scaffolds. Moreover, the increase in infiltration time also enhanced the compressive strength and toughness of the composite scaffolds because the infiltration thickness increased with infiltration time. The gradient structure resulted in a gradient degradation and may provide a better response to time-varying mechanical properties than pure β-TCP scaffolds during its absorption process. Therefore, composite scaffolds with a gradient are promising candidates for load-bearing bones or large segmental bone repair.